PROTECTION LAW HOLDER RIGHT CREATION FILM AGAINST THE SPREAD OF PIRATED FILMS THROUGH ILLEGAL STREAMING SITES - Bella Costa; Dewi Ayu Rahayu (Widya Gama Intellectual Property Rights, 2026)
The distribution of pirated films through illegal streaming websites constitutes a serious problem affecting copyright protection in Indonesia. This practice not only causes economic losses to copyright holders but also undermines the sustainability of the national film industry. This research aims to analyze the forms of legal protection available to film copyright holders and the legal liability of parties involved in the distribution of pirated films via illegal streaming platforms. This study employs normative legal research using a statutory approach by examining Law Number 28 of 2014 on Copyright, Law Number 33 of 2009 on Film, and other related regulations. The findings indicate that legal protection for film copyright holders is provided through preventive and repressive measures. Preventive measures include blocking illegal streaming websites, monitoring digital content, and enhancing public legal awareness. Repressive measures involve civil lawsuits for damages, termination of illegal distribution, and seizure of facilities used in copyright infringement. Furthermore, perpetrators of illegal film distribution may be held civilly liable under the Copyright Law and Article 1365 of the Indonesian Civil Code concerning unlawful acts. This research is expected to contribute to strengthen copyright protection for films and to encourage greater legal awareness within society in response to digital technological developments.